RESERVOIR ENGINEERING SENSITIVITY ANALYSIS WITH RANDOM FORESTS - ,, AKMAL AULIA (2015)
Sensitivity analysis is the act of assessing the impact of a list of parameters on a specific response. Reservoir engineering. like other engineering disciplines, typically requires a sensitivity analysis study in order to examine a particular system. Oneparameter- at-a-time (OP/\T), is a common method fiJr reservoir engineers. Here. each input parameter is perturbed based on the given range of values. whilst maintaining constant values fOr the remaining parameters. The design of experiments or sampling method of OPAT focuses on the local behaviour as opposed to the global behaviour. As of today, many works has been carried out in order to come up with a more global approach to sensitivity analysis.